DEVELOPMENT CIVILIZATION ISLAM INDONESIA ON TIME DUTCH OCCUPATION: PERADABAN ISLAM INDONESIA PADA MASA PENJAJAHAN BELANDA - Lena Lena Widia Astuti; Anjani Ayatus Sharifah; Nasikhin; Fihris (Transformasi : Jurnal Studi Agama Islam, 2023)
This paper describes the dynamics of the life of Muslims in Indonesia in the era of Dutch colonialism. In history, before Europeans came to Indonesia, Islam had developed in Indonesia and had been the majority religion since the 13th century on the island of Sumatra. There, an Islamic empire was established, namely Samudra Pasai, which was later transformed into the Darussalam Kingdom of Aceh, then, in the early 15th century, Islam had dominated the Malacca region (as the trade center of Southeast Asia). When Islam entered Indonesia, the spread of Islam began with Islamic scholars with great motivation. Apart from spreading Islam, they also traded. The important role of scholars can be traced on the map of Islamization which is directly proportional to economic development and the establishment of Islamic empires. In some areas it has become a trading center. International Muslims are becoming important exponents and creating communities in coastal areas. Through this society, Islam has been introduced to the people. But since the Dutch came to Indonesia, the trade situation changed changed. Dutch colonize Indonesia, even spread Islam stalled, because the clergy focused on the struggle against the Dutch.